2013
DOI: 10.1007/s12013-013-9701-x
|View full text |Cite
|
Sign up to set email alerts
|

Values of MMP-2 and MMP-9 in Tumor Tissue of Basal-Like Breast Cancer Patients

Abstract: Gelatinase A (MMP-2) and gelatinase B (MMP-9) are proteolytic enzymes involved in process of tumor invasion, and they are considered as possible tumor markers in breast cancer patients. In this study, we measured activity of latent and active form of MMP-2 and MMP-9 in tumor and adjacent tissue of 60 breast cancer patients by SDS-PAGE zymography. The activity of both form of gelatinases significantly increased with each advancing clinical stage of disease. ProMMP-9 and aMMP-9 activity in tumor tissue shows a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
27
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
6
27
0
1
Order By: Relevance
“…Evidently, this sharply contrasts with the high levels of expression of MMP-9 found in the cytoplasm of both HER2-positive and triple-negative breast cancers cells. Hence, our findings support the conclusions of recently published studies indicating a positive correlation between high levels of MMP-9 expression and triple-negative breast cancers [20, 38, 39]. Our results may also explain the findings of La Rocca et al who showed that high serum levels of MMP-9 are present in HER2 amplified breast cancers [40].…”
Section: Discussionsupporting
confidence: 92%
“…Evidently, this sharply contrasts with the high levels of expression of MMP-9 found in the cytoplasm of both HER2-positive and triple-negative breast cancers cells. Hence, our findings support the conclusions of recently published studies indicating a positive correlation between high levels of MMP-9 expression and triple-negative breast cancers [20, 38, 39]. Our results may also explain the findings of La Rocca et al who showed that high serum levels of MMP-9 are present in HER2 amplified breast cancers [40].…”
Section: Discussionsupporting
confidence: 92%
“…In patients with basal-like breast cancer, the activity of precursor and active forms of MMP-2 and MMP-9 was found to significantly increase with each advancing clinical stage of disease, and the activity of the precursor and active forms of MMP-9 in tumor tissue showed a positive association with tumor size. In addition, patients with lymph node involvement had higher activity of precursor and active forms of MMP-2 and the active form of MMP-9 than node-negative patients, and patients with steroid receptor-negative tumors had enhanced MMP-2 and MMP-9 activity compared with patients with luminal A tumors (16).…”
Section: Discussionmentioning
confidence: 93%
“…However, ectopic or excess MMP-9 activity degrades various components of the extracellular matrix, especially type IV collagen of the basement membranes. 15 Not surprisingly, overexpression of MMP-9 is observed in many cancers and is the leading cause of tumor progression, promoting tumor invasion and metastasis. 16 MMP-9 also is involved in the pathogenesis of inflammatory disorders, such as arthritis.…”
mentioning
confidence: 99%